PERAN GURU BK DALAM MENGATASI KECANDUAN OBAT TERLARANG (NARKOBA) PADA SISWA SMP NEGERI 1 PANTAI LABU - Mhd Yusuf Said; Nur Aini Batubara (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This study aims to determine the role of the BK teacher in overcoming drug addiction (narcotics) in SMP Negeri 1 Pantai Labu students. The research method uses qualitative. Data collected by interview, documentation, and observation. The results showed that: 1) The Principal of Labu Pantai 1 Junior High School had to provide complete facilities to BK teachers so that the implementation of guidance and counseling was more maximal and effective. 2) To BK teachers to be more professional in helping solve students' problems and collaborate with other teachers and invite anti-drug counseling agencies to come to school to better master and pay attention to student development so that the implementation of guidance and counseling is more effective.Keywords: BK teacher, addiction, illegal drugs.